Karakteristik Ekstrak Pewarna Alami Bunga Kenop (Gomphrena globosa L.) pada Perlakuan Ukuran Partikel dan Lama Maserasi serta Korelasi Antar Variabel - Ginting, Rahel Br; Wartini, Ni Made; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 3 (2020): SeptemberDO - 10.24843/JRMA.2020.v08.i03.p13, 2020)
Natural dyes from globe amaranth contain betacyanin obtained through the extraction process. This study aims to know the characteristics of natural dye extract globe amaranth on the treatment of particle size and maceration time as well as determine the correlation between total betacyanin with the yield and color intensity of natural dyes extract globe amaranth. This research used two factors namely, particle size (40, 60, and 80 mesh) and maceration time (24, 36 , and 48 hours). The data analysis used a bivariate correlation test. The results showed the characteristics of the natural dyes extract globe amaranth on the treatment of particle size and maceration time were as follows: yield 10.61–13.64 percent, total betacyanin 92.42–166.62 mg/100g, brightness level (L*) 18.03–13.09, redness level (a*) 8.29–10.62, and yellowish level (b*) 3.85-7.66. Total betacyanin and yield have a strong but not significant correlation, with a coefficient correlation (r) 0.6631 and coefficient determination (R 2 ) 0.4397. The correlation between total betacyanin with color intensity namely, brightness (L* ), redness (a* ), and yellowish (b*) has a very strong and correlation with the coefficient correlation (r) respectively -0.872; 0.877; and -8.836 and coefficient determination (R 2 ) respectively 0.7701; 0.7608; 0.7004. Keywords : Gomphrena globosa L ., betacyanin, corelation, nature dyes, extraction